Sport concussion assessment tool symptom anventory: Healthy and acute postconcussion symptom factor structure - Anderson, M.; Petit, K. M.; Bretzin, A. C.; Elbin, R. J.; Stephenson, K. L.; Covassin, T. (Journal of Athletic Training, 2020)
Context: Previous researchers have examined factor structures for common concussion symptom inventories. However, they failed to discriminate between the acute (<72 hours) and subacute (3 days-3 months) periods after concussion. The Sport Concussion Assessment Tool (SCAT) is an acute assessment that, when compared with other concussion symptom inventories, includes or excludes symptoms that may result in different symptom factors. Objective: The primary purpose was to investigate the symptom factor structure of the 22-item SCAT symptom inventory in healthy, uninjured and acutely concussed high school and collegiate athletes. The secondary purpose was to document the frequency of the unique SCAT symptom inventory items. Design: Case series. Setting: High school and college. Patients or Other Participants: A total of 1334 healthy, uninjured and 200 acutely concussed high school and collegiate athletes. Main Outcome Measure(s): Healthy, uninjured participants completed the SCAT symptom inventory at a single assessment. Participants in the acutely concussed sample completed the SCAT symptom inventory within 72 hours after concussion. Two separate exploratory factor analyses (EFAs) using a principal component analysis and varimax extraction method were conducted. Results: A 3-factor solution accounted for 48.1% of the total variance for the healthy, uninjured sample: cognitive-fatigue (eg, feeling "in a fog" and "don't feel right"), migraine (eg, neck pain and headache), and affective (eg, more emotional and sadness) symptom factors. A 3-factor solution accounted for 55.0% of the variance for the acutely concussed sample: migraine-fatigue (eg, headache and "pressure in the head"), affective (eg, sadness and more emotional), and cognitive-ocular (eg, difficulty remembering and balance problems) symptom factors. Conclusions: The inclusion of unique SCAT symptom inventory items did not alter the symptom factor structure for the healthy, uninjured sample. For the acutely concussed sample, all but 1 unique SCAT symptom inventory item (neck pain) loaded onto a factor.